Piezo-active composites : microgeometry-sensitivity relations /: microgeometry-sensitivity relations. ([2018]) - Topolov, Vitaly Yu (Vitaly Yuryevich), 1961-; Bowen, Christopher R (Christopher Rhys), 1968-; Bisegna, Paolo, 1968-
No abstract available